Long-term outcomes for Asian patients with X-linked hypophosphataemia: rationale and design of the SUNFLOWER longitudinal, observational cohort study. Issue 6 (29th June 2020) - Kubota, Takuo; Fukumoto, Seiji; Cheong, Hae Il; Michigami, Toshimi; Namba, Noriyuki; Ito, Nobuaki; Tokunaga, Shin; Gibbs, Yoshimi; Ozono, Keiichi
Abstract : Introduction: X-linked hypophosphataemic rickets/osteomalacia (XLH) is a chronic, debilitating genetic disease characterised by skeletal abnormalities and growth disorder. The burden of XLH begins in childhood and continues throughout life. Conventional medical therapy with phosphate, active vitamin D and surgery do not address the underlying pathophysiology of the disease. While treatment during childhood may improve bone deformity and growth retardation, a large proportion of adult patients still fail to reach normal stature. Furthermore, adult patients with XLH report comorbidities associated with unresolved childhood disease, as well as newly developed disease-related complications and significantly impaired quality of life (QOL). Despite the multiple negative aspects of XLH, Asian consensus statements for diagnosis and management are lacking. Methods and analysis: The Study of longitUdinal observatioN For patients with X-Linked hypOphosphataemic rickets/osteomalacia in collaboration With Asian partnERs study is a longitudinal observational cohort study of patients with XLH, designed to determine the medical characteristics and burdens (physical, emotional and financial) of this progressive disease and to evaluate the impact of treatment (including the use of burosumab) on clinical outcomes. The study was initiated in April 2018, and registration will remain open until 30 April 2022. The sample size planned for analyses is 160 patients, consisting of 100 patients in Japan and 60 patients in Korea. Up to 5 years of observation are planned per patient, from enrolment through to April 2023. Prospective and retrospective data will be collected to evaluate variables, including height/growth, rickets severity score, QOL, motor function and biomarkers for phosphate metabolism and bone turnover. Ethics and dissemination: Ethics approval was obtained from the Ethics Committee of Osaka University, the Ethics Committee of Kyowa Kirin Co and by the Ethics Committee of each participating medical institution. Two interim analyses and associated publications are planned using retrospective and enrolment data at year 1 and results at year 3. Trial registration numbers: NCT03745521 ; UMIN000031605.